Energy Consumption Reduction in the Condom Dipping Process: A Performance Comparison of Electric and Short-Wave Infrared Heating - Chimres, Nares; Pattanapradit, Utain; Suppalakpanya, Kittiphoom; Nikhom, Ruamporn (Engineering, Technology & Applied Science Research, 2025)
This study evaluates the energy performance of conventional Electric Heating (EH) and Short-wave Infrared Heating (SH) in the curing process of latex condoms. The findings demonstrate that SH significantly outperforms EH in terms of energy efficiency. Specifically, SH reduces energy consumption by 54.0%-71.7% for regular condoms and 38.8%-57.6% for thin condoms compared to EH. Both EH and SH meet the ISO 4074 standards for condom production, confirming that SH's efficiency gains do not compromise product quality. The consistent and superior energy performance of SH highlights its potential for improving cost-effectiveness and operational efficiency within the industry. While facilities currently using EH may achieve marginal benefits from upgrading to more advanced control systems, these improvements are relatively minor compared to the overall advantages offered by adopting the SH technology.